Letter from James Curtis Booth to his daughter, Margaret "Rita" Booth - Booth, James Curtis (1884)
James Curtis Booth (1810-1888) discusses a vacation to Atlantic City with his daughter, Rita.
Keywords: Booth, James Curtis, 1810-1888; New Jersey--Atlantic City; Vacations